Effect of 6-Benzylaminopurine, 2,4-Dichlorophenoxyacetic Acid and Indole-3-Butyric Acid on Micropropagation Stages of Achillea biebersteinii - Kahrizi, Danial; Kakaei, Mehdi (Asian Journal of Chemistry, 2010)
The yarrow (Achillea biebersteinii) is an important medicinal plant. Due to the limited plant material of this species, its micropropagation has been optimized in several stages. At first seeds placed on Murashig and Skoog medium in three different proportions (½, ¼ and complete Murashig and Skoog) for seed germination and seedling growth that ¼ Murashig and Skoog and Murashig and Skoog were best, for above, respectively. In direct shoot regeneration stage, the leaves have been placed on Murashig and Skoog medium supplemented with 6- benzylaminopurine (0, 2, 5 and 10 mg/L) that wasn't a significant difference for shoots regeneration and length average among 2, 5 and 10 mg/L 6-benzylaminopurine. For callus induction, there wasn't significant difference among 2, 4-dichlorophenoxyacetic acid concentrations (1, 2 and 5 mg/L) and 5 mg/L 6-benzylaminopurine was the best treatment for indirect regeneration. After elongation, in root induction stage, the young seedlings have been transferred to Murashig and Skoog medium supplemented with 0, 1, 2 and 4 mg/L indole-3-butyric acid that the 2 mg/ L indole-3-butyric acid had the best effect on root formation.